تفہیم القرآن (مولانا ابوالاعلی مودودی) اور تبیان القرآن (علامہ غلام رسول سعیدی) کا تقابلی مطالعہ : A comparative review of Tafheem Al-Qur’an (Maulana Abul Ali Maududi) and Tabiyan Al-Qur’an (Allama Ghulam Rasool Saeedi) - Dr. Muhammad Abubakar Siddique (Al Manhal Research Journal, 2023)
This article provides a comparative review of two renowned exegeses of the Holy Qur'an, namely Tafheem Al-Qur'an by Maulana Abul Ali Maududi and Tabiyan Al-Qur'an by Allama Ghulam Rasool Saeedi. The review analyzes and evaluates the similarities and differences between the two exegeses, including their approach, methodology, language, and content. The article highlights the significance of these works in shaping contemporary Islamic scholarship and their contributions to the interpretation of the Qur'an. The review also critically assesses the strengths and weaknesses of each exegesis, providing insights into their respective merits and demerits. Overall, this comparative review aims to provide a comprehensive analysis of the two exegeses and their impact on the understanding of the Holy Qur'an in the contemporary Islamic world.